2008
DOI: 10.2337/db07-0573
|View full text |Cite|
|
Sign up to set email alerts
|

A Central Role for Neuronal AMP-Activated Protein Kinase (AMPK) and Mammalian Target of Rapamycin (mTOR) in High-Protein Diet–Induced Weight Loss

Abstract: OBJECTIVE-A high-protein diet (HPD) is known to promote the reduction of body fat, but the mechanisms underlying this change are unclear. AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) function as majors regulators of cellular metabolism that respond to changes in energy status, and recent data demonstrated that they also play a critical role in systemic energy balance. Here, we sought to determine whether the response of the AMPK and mTOR pathways could contribute to the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
169
3
15

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(200 citation statements)
references
References 41 publications
5
169
3
15
Order By: Relevance
“…Indeed, hypothalamic AMPK is suppressed in response to central insulin, glucose, and leptin in mice, and stimulated in response to ICV infusion of the orexigenic agouti-related protein (15). mTOR and AMPK may in fact change in tandem to control energy status because ICV leucine administration causes decreased hypothalamic AMPK activity and increased mTOR activity in rodents (10), suggesting a complex balance between neural molecular signals. Another hypothalamic signal of nutrient status is IB kinase ␤ (IKK␤)/NFB, a mediator of inflammation normally quiescent in the hypothalamus, but activated in the setting of overnutrition (57).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…Indeed, hypothalamic AMPK is suppressed in response to central insulin, glucose, and leptin in mice, and stimulated in response to ICV infusion of the orexigenic agouti-related protein (15). mTOR and AMPK may in fact change in tandem to control energy status because ICV leucine administration causes decreased hypothalamic AMPK activity and increased mTOR activity in rodents (10), suggesting a complex balance between neural molecular signals. Another hypothalamic signal of nutrient status is IB kinase ␤ (IKK␤)/NFB, a mediator of inflammation normally quiescent in the hypothalamus, but activated in the setting of overnutrition (57).…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…These reports further confirmed that leucine-induced anorexia is dependent on hypothalamic mTORC1 activity and associated with the inhibition of AMPK. 17,18 Consistent with a cross-regulation between AMPK and mTORC1, the activation of these enzymes occurs in the same specific neuronal subtypes. 17 Furthermore, i.c.v.…”
Section: Introductionmentioning
confidence: 90%
“…17,18 Consistent with a cross-regulation between AMPK and mTORC1, the activation of these enzymes occurs in the same specific neuronal subtypes. 17 Furthermore, i.c.v. administration of leucine decreases mRNA levels of neuropeptide Y, [16][17][18] while increasing mRNA levels of POMC within the ARC.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations